Application of Occupational Therapy (Bead Weaving) in Patients with Auditory Hallucinations in the Larasati Ward of Dr. Arif Zainuddin Surakarta Psychiatric Hospital - Dewi Yusy Widianingrum; Ni Made Ayu Wulan Sari; Dayat Trihadi (NERSI: Jurnal Keperawatan Indonesia, 2025)
Mental health is a state of well-being that encompasses physical, psychological, and social aspects, and is not merely the absence of illness or disability. Mental disorders are serious mental health problems that can interfere with an individual's cognitive, affective, and social functioning. As a result, a person experiences difficulties in carrying out daily activities. One of the most common mental disorders is schizophrenia. Schizophrenia is a serious, chronic, and debilitating mental illness characterized by disorganized thinking, delusions, hallucinations, and strange or catatonic behavior. Auditory hallucinations are a stimulus disorder in which patients hear voices, especially human voices. Usually, patients hear people talking about what they are thinking and ordering them to do something. The purpose of this final nursing research paper is to overcome hallucination symptoms by applying occupational therapy (beading). The method used in this final nursing project is a descriptive case study explaining the nursing care provided over 5 days, including assessment, intervention by applying strategies such as scolding, controlling hallucinations, performing scheduled activities, and occupational therapy (bead stringing). From the evaluation results, the patient was able to recognize hallucinations, control hallucinations well, and reduce the frequency of hallucinations. The benefits for health services are to provide additional information on nursing services, improve service quality, and provide comprehensive nursing care for patients with mental disorders who experience auditory hallucinations. For the development of nursing science, it is hoped that this will enhance nurses' ability to provide nursing care and serve as an evaluation tool for nurses in delivering mental health nursing services. Keywords: mental health nursing care, auditory hallucinations, occupational therapy (stringing beads)